2008
DOI: 10.4049/jimmunol.181.12.8711
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Acquired Immune Response Reduces Coupled Bone Formation in Response to a Periodontal Pathogen

Abstract: Osteoimmunolgy involves the interaction of the immune system with skeletal elements. This interaction can lead to the formation of osseous lesions. To investigate how the acquired immune response could contribute to osteolytic lesions, we injected the periodontal pathogen Porphyromonas gingivalis adjacent to calvarial bone with or without prior immunization against the bacterium. Activation of the acquired immune response increased osteoclastogenesis and decreased coupled bone formation. The latter was accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
12

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 56 publications
(73 reference statements)
2
67
0
12
Order By: Relevance
“…TNF-a up-regulates the production IL-1b and IL-6 (Okada et al 1997, Dinarello 2000, Wajant et al 2003, Kwan Tat et al 2004, Garlet et al 2007, Musacchio et al 2009). TNF-a is also correlated with extracellular matrix degradation and bone resorption through actions promoting secretion of MMPs and RANKL (Graves & Cochran 2003, Garlet et al 2004) and coupled bone formation (Behl et al 2008). Accordingly, TNFa in circulation significantly impacts systemic inflammation and associated systemic conditions (CRP and CVD, obesity, Type 2 diabetes).…”
Section: Innate Immunity -The Inflammatory Responsementioning
confidence: 99%
“…TNF-a up-regulates the production IL-1b and IL-6 (Okada et al 1997, Dinarello 2000, Wajant et al 2003, Kwan Tat et al 2004, Garlet et al 2007, Musacchio et al 2009). TNF-a is also correlated with extracellular matrix degradation and bone resorption through actions promoting secretion of MMPs and RANKL (Graves & Cochran 2003, Garlet et al 2004) and coupled bone formation (Behl et al 2008). Accordingly, TNFa in circulation significantly impacts systemic inflammation and associated systemic conditions (CRP and CVD, obesity, Type 2 diabetes).…”
Section: Innate Immunity -The Inflammatory Responsementioning
confidence: 99%
“…Accordingly, the blockade of RANKL by OPG leads to a reduction of alveolar bone loss throughout experimental PD in mice (Jin et al, 2007). Appropriately, the coupled bone formation, which takes place under homeostatic conditions (Parfitt, 1982), seems to contribute to the conventional increased bone resorption in overall bone loss in PD (Behl et al, 2008). It has long been assumed that the host defense against microbial invasion and subsequent tissue destruction involves both innate and adaptive immunity cytokines.…”
Section: Periodontal and Periapical Tissues Under Inflammatory Conditmentioning
confidence: 99%
“…Curiously, the individual absence of innate immunity cytokines attenuates inflammatory bone loss; however their simultaneous inhibition results in more effective protection leading to almost complete remission of bone loss rate (Sartori et al, 2009, Graves & Cochran, 2003. In addition to a direct action toward bone resorption, innate immune cytokines also interfere with the coupled bone formation process (Behl et al, 2008). In fact, recent studies confirmed the early hypothesis that proinflammatory cytokines inhibit osteogenic differentiation (Ding et al, 2009, Lacey et al, 2009), and also demonstrate that activation of TLRs in osteoblasts induces the production of osteoclastogenic cytokines (Bar-Shavit, 2008).…”
Section: Classic Inflammatory Cytokines Role In Periodontal and Periamentioning
confidence: 99%
“…The local cellular effects of TNF-α include the adhesion of polymorph nuclear leukocytes (PMNs) to endothelial cells, degranulation of PMNs, activation of phagocytosis and intercellular adhesion molecule (ICAM) -1 expression. The amount of TNF-α was demonstrated at high levels in gingival crevicular fluid and diseased periodontal tissues [8,16] and experimental studies have shown a central role for TNF-α in alveolar bone resorption [31,32]. …”
Section: Th1 Cytokinesmentioning
confidence: 99%